ANALISIS USAHA DAN NILAI TAMBAH DARI USAHA PENGOLAHAN MARNING DAN EMPING JAGUNG DI KABUPATEN GROBOGAN - Shofia Nur Awami; Masyhuri Masyhuri; Lestari Rahayu Waluyati (Universitas Wahid Hasyim, 2013)
This research aimed (1) to calculate the income and the profit of corn processing home industry (2) to determine the amount of added value of corn processing home industry as marning and corn chips in Grobogan District. This research covered analysis methods several including, the income and the profit analysis, and the added value Analysis according Hayami, et.al. (1987). The results showed that the average monthly total revenue for corn processing production into corn chip Rp.5.264.225 with total cost Rp. 4.531.532,- so that it can be seen that the average profit earned by entrepreneur is Rp.732.692. Corn processing into marning, the average monthly total revenue production of Rp.5.583.888 with total cost of Rp. 5.139.657,- so that it can be seen that the average profit obtained entrepreneur is Rp. 444,285. The added value of processing corn into chips is Rp. 4.574 per kilogram and for marning Rp. 2.823 per kilogram. Key words: added value, corn processing home industry, income.